Landscape in change – place in uncertainty. A case study of detachment - Markuszewska, Iwona (Quaestiones Geographicae, 2024)
This paper discusses place-oriented values via actions against unwanted landscape changes reported by the community affected. The case study was based on a post-mining area in the city of Poznań (Poland), now functioning as a naturally valuable ecosystem. The relationships between landscape changes and the local community’s perception of these changes were studied. The results showed that a landscape transformation which is not accepted by the local community can stimulate a sense of loss, specifically, a feeling of detachment from the emotionally valued landscape. Based on this, a conceptual framework of detachment from a place was constructed. In this regard, the findings fill the gap in the case of experiences of solastalgia and topophobia. Different qualitative methods supported the analytical proceedings, such as content analysis, in-depth interviews, case study visits, community observation, field study and exploratory analysis.